Dr. Christina Yver — Deep Plane Facelift — Pittsburgh - Yver, Christina (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Christina Yver, practicing in Pittsburgh, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002976; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; pittsburgh